"Frank's sign" in a patient with pneumococcal pneumonia. Issue 7 (2015) - Mirijello, Antonio; Tosoni, Alberto; d'Angelo, Cristina; Ventura, Giulio; Cosmo, Salvatore De; Landolfi, Raffaele; Addolorato, Giovanni; Group, on behalf of Internal Medicine Sepsis Study
No abstract available